Ecological networks and corridors development in urban areas: An example of Tabriz, Iran - Mahmoudzadeh, Hassan; Masoudi, Hassan; Jafari, Firouz; Khorshiddoost, Ali Mohammad; Abedini, Asghar; Mosavi, Amir (Frontiers in Environmental Science, 2022)
Landscape fragmentation and the elimination of urban green spaces are the results of human activities which put significant pressure on urban sustainability. The planning and developing of urban ecological networks and corridors as an effective approach is a response to rapid urbanization and fragmentation of natural areas. The Tabriz metropolitan as the fourth-largest city in Iran was selected as a case study that has grown rapidly over the past few decades. This study presents a practical approach and framework for assessing and enhancing ecological connectivity of landscape. The framework was developed based on the landscape metrics, graph theory, least-cost modeling, and geographic information system (GIS) tools during three different periods (1984-2000-2020). The results using the values of landscape metrics such as CA, ED, MPS, MSI, LPI, NP, LSI, and COHESION indicate that the urban landscape of Tabriz has been more fragmented over the past three decades and has lost its connectivity. To reduce the effects of fragmentation and enhance landscape connectivity in study area, we proposed a network of ecological corridors that passes through the core ecological patches. Our results also indicate that the core patches and the least-cost created corridors are mainly located in the suburbs of Tabriz and the central part of the city cannot be suitable for ecological development. Therefore, using the above-mentioned methods could be an effective approach to develop ecological networks and improve landscape connectivity that can encourage urban planners and managers to protect and develop green networks.